2017
DOI: 10.1136/bcr-2016-218072
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of Bezold's and Citelli's abscesses, with recollection following an incomplete postoperative course of antibiotics

Abstract: Bezold's and Citelli's abscesses are rare complications of otitis media. We present a case of a 44-year-old Eastern European man, with a history of recurrent otitis media, who was admitted to hospital with mastoiditis and initially treated with antibiotics. Despite clinical improvement, a CT scan showed mastoiditis with Bezold's and Citelli's abscesses. The patient underwent a myringotomy and grommet insertion, in addition to a cortical mastoidectomy and curettage of the neck abscesses. After a good recovery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For instance, Smouha et al reported that four of their five patients diagnosed with Bezold’s abscess experienced delays in diagnosis (8). In addition, several of the patients featured in the present study’s case reports also experienced delays in detection and management (37,40,41). In the present study, the delay from acute symptom onset to diagnosis was 20.9 days, and the large variability (SD = 23.6 days) in time before diagnosis highlights how some patients may be at an increased risk of developing complications secondary to delayed treatment of Bezold’s abscess.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For instance, Smouha et al reported that four of their five patients diagnosed with Bezold’s abscess experienced delays in diagnosis (8). In addition, several of the patients featured in the present study’s case reports also experienced delays in detection and management (37,40,41). In the present study, the delay from acute symptom onset to diagnosis was 20.9 days, and the large variability (SD = 23.6 days) in time before diagnosis highlights how some patients may be at an increased risk of developing complications secondary to delayed treatment of Bezold’s abscess.…”
Section: Discussionmentioning
confidence: 84%
“…Of manuscripts written in non-English language, three had no abstracts available, and five provided abstracts with insufficient data regarding baseline demographics, clinical presentation, and management. Finally, 45 studies were included in this systematic review, with 49 patients being pulled from case reports or series (1,3,8–50).…”
Section: Resultsmentioning
confidence: 99%